2021
DOI: 10.1097/corr.0000000000001969
|View full text |Cite
|
Sign up to set email alerts
|

International Validation of the SORG Machine-learning Algorithm for Predicting the Survival of Patients with Extremity Metastases Undergoing Surgical Treatment

Abstract: Background The Skeletal Oncology Research Group machine-learning algorithms (SORG-MLAs) estimate 90day and 1-year survival in patients with long-bone metastases undergoing surgical treatment and have demonstrated good discriminatory ability on internal validation. However, the performance of a prediction model could potentially vary by race or region, and the SORG-MLA must be externally validated in an Asian cohort. Furthermore, the authors of the original developmental study did not consider the Eastern Coope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Additionally, the Brier score of a prediction model must be compared with the null model that ignored all the covariates, with a Brier score lower than the null model indicating better algorithm performance. 27 In this study, all the constructed prediction models had lower Brier scores than the corresponding null models. A significant difference was defined as a two-sided P value of ≤ 0.05.…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, the Brier score of a prediction model must be compared with the null model that ignored all the covariates, with a Brier score lower than the null model indicating better algorithm performance. 27 In this study, all the constructed prediction models had lower Brier scores than the corresponding null models. A significant difference was defined as a two-sided P value of ≤ 0.05.…”
Section: Discussionmentioning
confidence: 55%
“…In order to aid decision making, some models to predict survival in bone metastasis patients with impending or pathological fractures have been developed in the past [ 13 , 15 , 16 ], including the 2013-SPRING model [ 17 ]. Their validation—both internally and externally—is necessary in order to evaluate whether models tend to over- or underestimate remaining prognosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to estimate prognosis of bone metastasis patients with impending or pathological fractures prior to surgery, some prognostic models have been developed in the past. These include the (modified) Bauer Score for spinal lesions [ 11 , 12 ], the SORG Machine-Learning Algorithm (SORG-MLA) [ 13 ] and OPTIModel [ 14 ] for both spinal and extremity metastases, as well as the PATHFx model [ 15 ], the 2008-SPRING model [ 16 ] and its updated version, the 2013-SPRING model for extremity lesions [ 17 ]. The latter model uses readily available clinical variables in order to estimate patients’ survival probability within 3, 6 and 12 months after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been recently updated to the 3rd version (3) to provide predictions for patients treated both operatively and with radiation only. However, some studies suggested PSSs could perform differently between ethnogeographically distinct cohorts (4,5,(8)(9)(10)(11)(12), and they should have been validated before being applied onto a specific population. The PATHFx offers survival predictions at 6 different time points: 1, 3, 6, 12, 18, and 24 months.…”
mentioning
confidence: 99%